Building number sense: A systematic literature review of mathematical concept development in early years - M. Zainul Arifin; Cyndana Kartika Putri; Laila Mubarakah (KALAMATIKA Jurnal Pendidikan Matematika, 2026)
Many early mathematics programs emphasize the importance of number sense as a basic skill; however, there is a lack of comprehensive reviews that integrate effective strategies and concepts used in early childhood education contexts. This study aims to conduct a systematic review of various approaches, strategies, and learning methods for developing number sense in early childhood, identify the most frequently studied mathematical concepts, and analyze the factors that influence their effectiveness. A Systematic Literature Review (SLR) method was applied, involving twelve peer-reviewed journal articles selected from the Scopus database using the PRISMA. It was found that game-based learning, the use of multiple representations, digital technology, exploratory activities, and problem-solving tasks are frequently used to support the development of number understanding. The main mathematical concepts identified include cardinality, number representation, basic operations, quantity structure, and early reasoning. Effectiveness is influenced by teacher competence, student engagement, teaching strategies, and the learning environment. This study contributes to a deeper understanding of early numeracy development and highlights the importance of designing child-centered, adaptive, and experience-based learning. These findings can serve as a reference for early childhood educators, curriculum developers, and policymakers in improving mathematics instruction at the early education level.